2016
DOI: 10.1111/bjso.12160
|View full text |Cite
|
Sign up to set email alerts
|

Global identification predicts gay–male identity integration and well‐being among Turkish gay men

Abstract: In most parts of the world, hegemonic masculinity requires men to endorse traditional masculine ideals, one of which is rejection of homosexuality. Wherever hegemonic masculinity favours heterosexuality over homosexuality, gay males may feel under pressure to negotiate their conflicting male gender and gay sexual identities to maintain positive self‐perceptions. However, globalization, as a source of intercultural interaction, might provide a beneficial context for people wishing to create alternative masculin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 89 publications
3
42
0
Order By: Relevance
“…Previous research has shown that it is difficult to prime global identification directly among Turkish gay men (Koc & Vignoles, 2016). Here, rather than directly priming the identification, we aimed to foster (vs. undermine) identification by priming awareness of positive (vs. negative) aspects of globalisation.…”
Section: Overview Of the Present Research And The Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has shown that it is difficult to prime global identification directly among Turkish gay men (Koc & Vignoles, 2016). Here, rather than directly priming the identification, we aimed to foster (vs. undermine) identification by priming awareness of positive (vs. negative) aspects of globalisation.…”
Section: Overview Of the Present Research And The Hypothesesmentioning
confidence: 99%
“…For Turkish identification, we did not make any specific predictions. For religious identification, based on previous evidence that religiosity is associated with the incompatibility of gay and male identities among Turkish gay men (Koc & Vignoles, 2016), we hypothesized that religious identification here would predict lower levels of gay-male identity integration (H6) and access to gayaffirmative social contexts (H7).…”
Section: Overview Of the Present Research And The Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations